The Quantum Chemical and QSAR Studies on Acinetobacter Baumannii Oxphos Inhibitors - Sayıner, Hakan Sezgin; Abdalrahm, Afaf A. S.; Başaran, Murat A.; Kovalishyn, Vasyl; Kandemirli, Fatma (Bentham Science Publishers Ltd., 2018)
Acinetobacter is a Gram-negative, catalase-positive, oxidase-negative, non-motile, and no fermenting bacteria.In this study, some of the electronic and molecular properties, such as the highest occupied molecular orbital energy (EHOMO), lowest unoccupied molecular orbital energy (ELUMO), the energy gap between EHOMO and ELUMO, Mulliken atomic charges, bond lengths, of molecules having impact on antibacterial activity against A. baumannii were studied. In addition, calculations of some QSAR descriptors such as global hardness, softness, electronegativity, chemical potential, global electrophilicity, nucleofugality, electrofugality were performed.The descriptors having impact on antibacterial activity against A. baumannii have been investigated based on the usage of 29 compounds employing two statistical methods called Linear Regression and Artificial Neural Networks.Artificial Neural Networks obtained accuracies in the range of 83-100% (for active/inactive classifications) and q2=0.63 for regression.Three ANN models were built using various types of descriptors with publicly available structurally diverse data set. QSAR methodologies used Artificial Neural Networks. The predictive ability of the models was tested with cross-validation procedure, giving a q2=0.62 for regression model and overall accuracy 70-95 % for classification models.
Keywords: Acinetobacter baumannii; QSAR; E. coli; Quantitative Structure-Activity Relationship; Microbial Sensitivity Tests; dragon; DFT; gram-negative bacteria; Oxidative Phosphorylation; Anti-Bacterial Agents; Inhibitory Concentration 50; Linear Models; Anisotropy; Quantum Theory; Benzimidazoles; Neural Networks, Computer; A. baumannii; artificial neural networks; 13. Climate action